Actions to combat student dropout in higher education - Andressa Sasaki Vasques Pacheco; Marcelo Ferreira Tete; Sandro Eduardo Monsueto (Avaliação: Revista da Avaliação da Educação Superior)
Abstract The phenomenon of dropout presents a significant challenge to higher education institution managers, as it is influenced by various aspects, making it complex and difficult to understand. Therefore, the objective was to analyze actions and interventions to combat dropout rates in Brazilian public federal universities. Regarding methodological procedures, the research is classified as descriptive, applied, qualitative and quantitative, bibliographic, and a multiple case study. The data used were primarily from a study conducted by the Brazilian Federal Court of Accounts (TCU, 2023). It was found that 60% of the institutions have an institutional policy related to combating student dropout. Although most have access to student profile data, few use this information in a more proactive and predictive manner. Concerning actions, a survey was conducted based on theory and research with all federal universities through the TCU. With this data, it was possible to verify that a wide variety of actions are carried out, with 43 being compiled.